Persistent US current account deficit: The role of foreign direct investment - Kaan Celebi; Werner Röger; Paul J. J. Welfens (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
This paper re-evaluates the US external deficit which has considerably widened over the 1990s. US safe asset provision to the rest of the world is the dominant explanation for the persistent nature of the US external deficit. We suggest that apart from the safe asset hypothesis, there is an important role for technology shocks originating in US multinational companies that have a strong foreign direct investment presence. It is shown that technology shocks that increase the market value of FDI assets are loosening the sustainability constraint on the trade balance and therefore generate persistent trade balance deficits. Our analysis suggests that this channel can explain why the US tech-boom in the 1990s has contributed significantly to the increase of the US current account deficit and its duration. Technology shocks have been neglected as a reason for longer lasting current account deficits since for these shocks, standard open economy DSGE models can only generate temporary external deficits. We show that our enhanced DSGE-model - covering both trade and FDI - not only matches well the dynamics of the US external balance but can also account for the observed evolution of FDI related components of the external balance. In particular, US technology shocks can match the increase in net FDI income and a rising FDI capital balance. Our analysis suggests that FDI flows and their determinants should play a more important role in monitoring external imbalances by international organizations.
Keywords: D5; F21; F23; F32; O3; 330; foreign direct investment; current account imbalance; USA; DSGE; technology shocks